A Mystery Unsolved: A Spontaneous Lens and Uveal Prolapse in a New-born: Poster Presentation - Case Report - Resident - NABILA ALJUFRI; Shafiq Advani; Dany Petra; Agnesstacia Vania L; Yulia Aziza; Julie D Barliana; Rio Rhendy (Majalah Oftalmologi Indonesia, 2023)
Introduction : Corneal rupture in new-born, especially during the first week of life is rare. Some of these cases occur because of ocular trauma during deliveries, systemic infection, and congenital anomalies. We aim to deliver a rare case of spontaneous lens and uveal prolapse in new-born and management in treating the case. Case Illustration : A-2-day-old full-term-baby was referred due to bleeding of the right eye 6 hours post-partum by spontaneous vaginal delivery with no trauma. The mother, a 23-year-old, having the second born with no history of medical illness or vaginal discharged during pregnancy. Measurements of birth weight and length were normal. Eye examination of the right eye (RE) was uveal and lens prolapse and left eye (LE) cloudy cornea with leukoma and prominent neovascularization. Orbital CT-Scan revealed bilateral vitreous bleeding of both eyes. Laboratory examination showed reactive IgM for herpes simplex virus, reactive IgG for both toxoplasma and rubella. Corneal swab culture was sterile. Systemic and topical antibiotics were administered then switched to systemic antivirus. The 12-day-old-patient showed partial epithelization of cornea, less uveal volume with it partially shrank. Close observation was conducted and evisceration was postponed. Discussion : Although etiologic work-up has been addressed, exact etiology remains unknown with the possibility of congenital cause. It has been postulated that structurally malformed eyes are more prone to corneal perforations. Management should be personalized based on the patient’s need. Conclusion : Thorough examination is vital a rare case with undisclosed aetiology especially new-born. Patient monitoring is sufficient if no infections and bleedings found.